Analysis of Students’ Mathematical Errors Based on Newman Error Analysis (NEA) in Terms of Learning Style - Wanda Nugroho Yanuarto (THETA: Jurnal Pendidikan Matematika, 2021)
This article aims to analyze students' mathematical errors from the written test of quadrilateral story problems. Students' mathematical errors were analyzed using the Newman Error Analysis (NEA) method. These mathematical errors are viewed from the student's learning style. This type of research is a qualitative descriptive study. The subjects of this study were students of class VII SMP Negeri 1 Sumbang in the 2016/2017 academic year. Students are grouped into 3 groups of visual, auditorial, and kinesthetic learning styles. Data collection techniques in this study used learning style questionnaires, quadrilateral written tests, interviews, and documentation. The results of this study indicate that students who have a visual learning style tend to experience errors at the problem reading, transformation, process skills, and inference stages. Students who have an auditory learning style tend to experience errors at the stage of understanding the questions, transformation, process skills and conclusions. Students who have a kinesthetic learning style have a tendency to make mistakes at all stages, namely reading questions, understanding questions, transformation, process skills and in the conclusion stage